Customer Relationship Management Dalam Meningkatkan Loyalitas Pelanggan Pada Doorsmeer Keluarga Nasution Menggunakan Metode Algoritma K-Means - Billy Hendrik; Lubis, Siti Sahara; Lubis, Fitri Sari (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2023)
Doorsmeer, the Nasution Family, which is located on Jl. Medan Padang Aek Godang Panyabungan, Mandailing Natal Regency, provides services in the form of car and motorcycle washing. Bookkeeping at the Nasution Family Doorsmeer is still done manually, allowing for loss of important transaction data, as well as a lack of business promotion in the community resulting in slow business development. The purpose of this study is generally to apply Web-based Customer Relationship Management with the K-means algorithm method for marketing/transactions at the Nasution Family Doorsmeer. This research is a combined type, using descriptive qualitative and quantitative methods. From the research results it is known that with the existence of Web-based Customer Relationship Management it can simplify and assist in managing good marketing strategies so as to increase sales revenue, and by providing the best service will encourage customer loyalty. In determining loyal customers the fields used are the customer's name, vehicle license plate, number of visits and total transactions for 2 months, then the data will be processed with the k-means clustering algorithm. The final result with 20 samples of transaction data is the final result with 2 clusters, namely, cluster 1 (C1) with 13 disloyal customers, cluster 2 (C2) with 7 loyal customers. By implementing Customer Relationship Management with K-Means, you can build customer clustering to categorize customers who use services so that service providers can identify the characteristics of their customers. With Customer Relationship Management with K-Means, promotions can be directed to customers who are entitled to get them. With the implementation of Customer Relationship Management reaches more new customers through a system that has been directly integrated with the internet network, so that new visitors or those who do not know Doorsmeer Nasution Family, both those around the business location and those who are far away, will find it easy to get to know Doorsmeer Nasution Family through internet searches so that the number customers who transact with the Nasution Family's Doorsmeer business have increased.